New Definition of Ultrafine Particles in Mine Paste and Its Relationship with Rheological Properties. (3rd May 2021) - Xie, Jincheng; Qiao, Dengpan; Han, Runsheng; Deng, Tao; Wang, Jun
Abstract : Mine backfill paste is generally composed of tailings and coarse aggregates. In engineering practice, the definitions in fill material classification are vague. In this paper, the size range of ultrafine particles is defined by the Stokes sedimentation test and hydraulic coarseness method. The size range of ultrafine particles is affected not only by the geometric size of the particles but also by the physical characteristics of the particles themselves. This definition has more comprehensive considerations and stricter physical and mathematical significance than the traditional definition of ultrafine particles based only on size. There is a strong correlation between ultrafine particles in fill materials and the rheological properties of the mine backfill paste. In this study, through experiments and correlation analysis, it was found that the content of ultrafine particles is positively correlated with the plastic viscosity of the mine backfill paste, and its growth range is exponential. The coarse aggregate content is positively correlated with the yield stress of the mine backfill paste. A regression analysis model was established for the rheological properties of mine backfill paste. The model has few factors and high correlation, so it can simply and efficiently predict the rheological properties of mine backfill paste and guide engineering practice.